Frequency of metastases within the hypothalamic–pituitary area and the associated high-risk factors in patients with brain metastases - Xie, Peng; Hu, Huiling; Cao, Xiong; Lan, Ning; Zhang, Huanyu; Yan, Ruifeng; Yue, Peng; Hu, Wenteng; Qiao, Hui (Frontiers in Neurology, 2023)
Objective: Brain radiotherapy often results in impairment of hypothalamic-pituitary (HT-P) function, which in turn causes secretory dysfunction of related hormones. In this paper, the frequency of metastasis in the HT-P area and its high-risk factors in patients with brain metastasis were retrospectively analyzed, and thus provide experimental evidence for protecting HT-P area during whole brain radiotherapy (WBRT). Methods: A retrospective analysis was performed on the data of patients with brain metastasis diagnosed by cranial magnetic resonance imaging (MRI) at the First Hospital of Lanzhou University from 2017 to 2020. The anatomical positions of the hypothalamus and pituitary were delineated, followed by their expansion by 5mm outwards respectively in the three-dimensional direction, and the hypothalamus + 5mm and pituitary + 5mm were obtained as the avoidance area, in which the frequency of brain metastasis was evaluated. Univariate and multivariate logistic regression models were used to analyze the high risk factors of brain metastasis in HT-P area. Results: A total of 3,375 brain metastatic lesions from 411 patients were included in the analysis. The rates of brain metastasis in the hypothalamus +5mm and pituitary +5mm in the whole group of cases were 2.9% (12/411) and 1.5% (6/411) respectively; the frequency of lesions was 0.4% (13/3375) and 0.2% (6/3375) respectively. Univariate and multivariate analyses showed that the number of brain metastases (OR = 14.946; 95% CI = 4.071–54.880; P < 0.001), and the occurrence of brain metastasis in the pituitary(OR = 13.331; 95% CI = 1.511–117.620; P = 0.020) were related to brain metastasis in the hypothalamus, and that the only relevant factor for brain metastasis in the pituitary was the occurrence of that in the hypothalamus (OR = 0.069; 95% CI = 0.010–0.461; P = 0.006). Conclusion: The frequency of brain metastasis in the HT-P area is extremely low. The risk of brain metastases in the hypothalamus is correlated with their number. The larger the number of metastatic lesions, the higher the frequency of brain metastasis. Protection of the HT-P area during WBRT may be unlikely to compromise the tumor recurrence rate for patients with a relatively small number of brain metastases.